Reconstruction Of Performance Measurement Models For Mental Hospitals - Novitasari, Etika; Maharani, Satia Nur; Wardoyo, Cipto (Asia Pacific Journal of Management and Education (APJME), 2020)
The purpose of this study is to build a performance measurement model which appropriate with the characteristics of the RSJ. This research uses a qualitative case study approach. The results showed that the RSJ used the BSC performance measurement, while the BSC was limited to four perspectives. So that there is an important aspect that has not been included in the BSC, namely the aspect of care. Nurse care for patients, organizational care for employees and patients as well as additional spiritual healing to accelerate patient recovery. The performance measurement model proposed by the researcher is directly based on the organizational goals of RSJ, it is expected that the performance measurement model that is directly executed from the goal will directly impact the achievement of targets without neglecting the values that have been adopted by RSJ.